FACTORS AFFECTING CONVERSION WETLAND INTO OIL PALM - Rangkuti, Khairunnisa; Siregar, Sasmita; Lestari, Reni (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
This study aimed to analyze the influence of income, agricultural risk, the selling price, cost of production and availability of water for the conversion of rice land into palm oil ,. The data used in this study are primary data and secondary data. The sampling method using Random Sampling is taking a random sample by strata. Data analysis method used is multiple linear analysis. The result is a coefficient of determination (R-Square) 0.91. This value indicates that simultaneously (synchronously) wetland conversion into oil palm plantations are affected by revenue, selling prices, agricultural risk, the cost of production and availability of water by 91% and the rest influenced by other factors beyond the variables that are not tested by 9%, Most variable production costs significantly affect wetland conversion to oil palm plantations. While the variable income, sales price, the risk of agriculture and availability of water does not significantly influence wetland conversion to oil palm plantations.Â Keywords: Land conversion, Palm land, rice land